ISPC Commentary on the Revised Proposal for CRP4 - November 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the Revised Proposal for CRP 4: Agriculture for Improved Nutrition & Health (Revision of October 2011).